Abu al-Ma'ali al-Juwaini's Contribution to Maqashid al-Shari'ah Thought in Kitab al-Burhan Fi Ushul al-Fiqh - Heru Susanto; Agustina Kumala Dewi (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2024)
This study examines al-Juwaini’s thought on maqashid al-shari'ah and its contribution to the development of the discipline of maqashid al-shari'ah. This study uses a type of qualitative literature research with content analysis. The results of the research are as follows: First, al-Juwaini contributed his thought in the field of maqashid al-shari'ah by formulating the formulation of ushul al-shari'ah. Al-Juwaini uses several terms that refer to the meaning of the shari'a objectives as follows: al-ma'ani, al-hikmah, murad al-shari', al-ghard and al-aghrad, al-mashalih, mahasin al-shari'ah, mathalib al-shari'ah, bughyah al-shari' and mabaghi al-shar', al-kulliyyat and kulliyyat al-shar', al-qa'idah al-kulliyyah and qawa'id al-shari'ah. Second, Al-Juwaini divides ushul al-shari'ah into 5 (five) categories, (1) Shari'ah of the primary category (amr daruriyy) and can be reasoned by aql (ma’qulah al-ma’na); (2) Shari'ah related to general needs (al-hajah al-'ammah); (3) Shari'ah of the tertiary category (makramah) and is not part of amr daruriyy or hajah 'ammah; (4) Shari'ah of encouragement category (mandub) and is not related to the primary (daruriyyah) and secondary (hajiyyah; (5) Shari'ah whose meaning is 'universally (kulli) can be known by ‘aql, but specifically (juz'i) cannot be reasoned. Third, the formulation then became the embryo and foundation for subsequent maqashid scholars such as al-Ghazali and al-Shatibi in the development of the maqashid al-shari'ah as it is known today, namely the concepts of daruriyyah, hajiyyah, and tahsiniyyah as well as the conception of al-daruriyyat al-khamsah. So it can be said that al-Juwaini was the initiator and the first scholar to carry out the conception of maqashid al-shari'ah.